2001
DOI: 10.1097/00005392-200107000-00094
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vitamin E on the Response of the Rabbit Bladder to Partial Outlet Obstruction

Abstract: These data indicate that a major etiology of bladder dysfunction secondary to partial outlet obstruction is related to free radical generation and resultant membrane lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Perhaps this situation can be interpreted as the adaptation of the bladder tissue to ischemia-reperfusion on the biochemical basis. Although it has been demonstrated that ischemiareperfusion injury may lead to structural changes in bladder wall and may play an important role in the bladder dysfunction in the acute and chronic urinary retention following catheterization [2][3][4][5], we think that our data, only interpreting ROS, are not sufficient to make a comment clinically in two episodes of urinary retention.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Perhaps this situation can be interpreted as the adaptation of the bladder tissue to ischemia-reperfusion on the biochemical basis. Although it has been demonstrated that ischemiareperfusion injury may lead to structural changes in bladder wall and may play an important role in the bladder dysfunction in the acute and chronic urinary retention following catheterization [2][3][4][5], we think that our data, only interpreting ROS, are not sufficient to make a comment clinically in two episodes of urinary retention.…”
Section: Discussionmentioning
confidence: 81%
“…In order to examine the effects of acute urinary retention on the morphology and physiology of the bladder, various obstruction models have been developed on various types of animal subjects. Though there were significant differences between the species regarding bladder size, capacity, compliance and physiology, their responses to obstruction were similar [4]. ROS, developed in the tissue that had long been ischemic, leads to tissue damage due to ischemia or lipid peroxidation in cell membrane.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Potassium citrate again was found to limit stone recurrence after extracorporeal shockwave lithotripsy [7], and as highly potent antioxidant agents, allopurinol and vitamin E have been used to minimize free oxygen radical-induced alterations in certain tissues by inhibiting ROS formation [11,13,14,21].…”
Section: Discussionmentioning
confidence: 99%
“…While verapamil and nifedipine (calcium channel blocking agents) were found to limit the histologic changes as well as crystal deposition induced by certain renal trauma [8,11,12], potassium citrate was found to limit stone recurrence after extracorporeal shockwave lithotripsy [7], and allopurinol as well as vitamin E has been used as antioxidant agents to minimize the effects of free oxygen radical formation in certain tissues [11,13,14].…”
Section: Introductionmentioning
confidence: 99%